Muscle size of individual hip extensors in sprint runners: Its relation to spatiotemporal variables and sprint velocity during maximal velocity sprinting - Takahashi, K.; Kamibayashi, K.; Wakahara, T. (PLOS ONE, 2021)
Hip extensor muscle size is related to sprint running performance. However, the mechanisms underlying this relationship remain unclear. To gain insights into this issue, the present study examined the relationships between the individual hip extensor sizes, spatiotemporal variables (step frequency and length, and their determinants), and sprint velocity during maximal velocity sprinting. Magnetic resonance images of the hip and right thigh were obtained from 26 male sprinters to determine the volumes of the gluteus maximus, individual hamstrings and adductors, and gracilis. Muscle volumes were normalized to their respective body mass and recorded as relative muscle volumes. The sprinters performed a 100-m sprint with their maximal effort. Their sprint motions were recorded using cameras to calculate the mean sprint velocity and the spatiotemporal variables at 50-60 m interval. The sprint velocity was significantly correlated with the relative volume of the semitendinosus (r = 0.497, P = 0.010), but not with the volumes of the other examined muscles. The relative volume of semitendinosus significantly correlated with the stance distance (r = 0.414, P = 0.036) and the stance distance adjusted by the stance time (r = 0.490, P = 0.011). Moreover, there were significant correlations between the stance distance and step length (r = 0.592, P = 0.001), and between the step length and sprint velocity (r = 0.509, P = 0.008). These results suggest that the semitendinosus contributes to attaining long stance distance and thereby high sprint velocity during maximal velocity sprinting.